STEGANOGRAPHY TECHNIQUE ON CLOSED 3D TRIANGULAR MESHES - Thái Duy Quý (Tạp chí Khoa học Đại học Đà Lạt)
This paper proposes a structure presentation of 3D mesh and closed mesh, which can apply for hidden messages. Based on shifting value coordinates of vertices, the technique allows information hidden on the triangular 3D mesh model. This above process is controled by rule secret key. The article also mentions a reverse to decode data from stego.